On the dynamics of a smart tensegrity structure using shape memory alloy - Martins, Daniel [UNESP]; Paupitz Gonçalves, Paulo José [UNESP] (IOP Publishing, 2019)
A tensegrity system is composed by two types of elements, tensile and compressive parts, which promotes the structural stability of the system, in this case the tensile parts are cables (steel cables), and the compressive parts are bars made of steel. An attractive characteristic of a tensegrity structure is the capability to be deployable, for this reason, is interesting for space applications due to the small volume that occupy in a possible transport to a station outside the earth. In general, these structures can be large with many repetitive cells. In this work, a tensegrity boom structure consisting of ten periodic cells made of bars and cables is studied. The numerical model, obtained by finite element method, is validated experimentally considering the case of one structural cell. In order to make the system adaptable to external excitation, one of the steel cables in the tensegrity is replaced by a SMA (shape memory alloy) cable (nitinol) allowing the dynamics characteristics of the system to be changed according to an electrical current applied SMA. Various configurations for placing the SMA cable are studied with the objective of reducing the vibration amplitudes for harmonic force excitation.